Adherence to dietary approaches to stop hypertension diet may modify fat mass and fat free mass indexes in apparently healthy adults - Rahimi, Mohammad Hossein; Mohammadi, Farzad; Mollahosesini, Mehdi; Yekaninejad, Mir Saeed; Maghbooli, Zhila; Mirzaei, Khadije (Progress in Nutrition, 2019)
Background: The anatomic site of increased body fat is important because of its effects on the body. DASH diet have positive effects on body composition through its effects on weight. Our objective of this investigation was to assay the effects of adherence to DASH diet on body fat distribution. Methods: A total of 256 healthy participants were included in the current cross-sectional study. Complete body composition analysis was done whereby for all the cases. BC-418MA (Tanita UK Ltd, Middlesex, United Kingdom) was used. Dietary intake was assessed with a semi-quantitative food frequency questionnaire that consisted of 147 foods and beverages (with standard serving sizes commonly consumed by Iranians. We constructed the DASH score based on 8 foods and nutrients. FM and FFM indexes defined based on fat mass and free fat mass. Results: Obese individuals with more adherence to DASH diet had lower FFMI (P=0.04). Lowe trunk fat was strongly associated to more adherence to DASH diet (P=0.02). Moreover, individuals those had more adherence to DASH diet had lower waist circumference (P=0.03). Conclusions: The current study suggests that adherence to DASH diet is highly associated with weight loss in obese individuals and may be associated to FMI and FFMI which is depended to sex.